Modulation of Iron Import and Metronidazole Resistance in Bacteroides fragilis Harboring a nimA Gene - Paunkov, Ana; Sóki, József; Leitsch, David (Frontiers in Microbiology, 2022)
Bacteroides fragilis is a commensal of the human gut but can also cause severe infections when reaching other body sites, especially after surgery or intestinal trauma. Bacteroides fragilis is an anaerobe innately susceptible to metronidazole, a 5-nitroimidazole drug that is prescribed against the majority of infections caused by anaerobic bacteria. In most of the cases, metronidazole treatment is effective but a fraction of B. fragilis is resistant to even very high doses of metronidazole. Metronidazole resistance is still poorly understood but the so-called nim genes have been described as resistance determinants. They have been suggested to encode nitroreductases which reduce the nitro group of metronidazole to a non-toxic aminoimidazole. More recent research, however, showed that expression levels of nim genes are widely independent of the degree of resistance observed. In the search for an alternative model for nim-mediated metronidazole resistance, we screened a strain carrying an episomal nimA gene and its parental strain 638R without a nim gene for physiological differences. Indeed, the 638R daughter strain with the nimA gene had a far higher pyruvate-ferredoxin oxidoreductase (PFOR) activity than the parental strain. High PFOR activity was also observed in metronidazole-resistant clinical isolates, either with or without a nim gene. Moreover, the strain carrying a nimA gene fully retained PFOR activity and other enzyme activities such as thioredoxin reductase (TrxR) after resistance had been induced. In the parental strain 638R these were lost or very strongly down-regulated during the development of resistance. Further, after induction of high-level metronidazole resistance, parental strain 638R was highly susceptible to oxygen whereas the daughter strain with a nimA gene was hardly affected. Ensuing RT-qPCR measurements showed that a pathway for iron import via hemin uptake is downregulated in 638R with induced resistance but not in the resistant nimA daughter strain. We propose that nimA primes B. fragilis towards an alternative pathway of metronidazole resistance by enabling the preservation of normal iron levels in the cell.